Hepatoprotective effect of a novel lactic acid‐fermented garlic extract functional food product against acute liver injury. Issue 2 (5th January 2020) - Kim, Tae Min; Kim, Ki Hoon; Jo, Jeong Hyun; Park, Joonghoon; Kwon, Yong Sam; Yang, Je Hoon
Abstract: Lactic acid‐fermented garlic extract (LAFGE) has been shown to have hepatoprotective role in liver diseases. This study was conducted to evaluate the efficacy of a new LAFGE‐based hepatoprotective functional food product (named D‐18‐007) formulated with other additive components, including l ‐arginine, l ‐ornithine, and the leaf extract of licorice and artichoke. In a rat model of d ‐galactosamine(GalN)/LPS‐induced liver injury, the survival was significantly higher in animals treated with D‐18‐007 than in animals treated with LAFGE. The hepatic injury was alleviated by either LAFGE or D‐18‐007, but the overall effect was more significant in D‐18‐007, as shown by the necrosis, histology, and serum analyses. Also, the decrease in GalN/LPS‐induced lipid peroxidation in the liver tissue was more significant in D‐18‐007 than LAFGE. The decrease in IL‐6 protein in the liver was similar between LAFGE and D‐18‐007. Moreover, we compared the amount of the bile in normal animals and found that D‐18‐007 has better choleretic activity than LAFGE. Using this acute liver injury model, our results suggest that D‐18‐007 has an enhanced hepatoprotective effect in acute liver injury compared with LAFGE alone. Abstract : In this study, we evaluated the efficacy of a lactic acid‐fermented garlic extract‐based hepatoprotective functional food formulated with l ‐arginine, l ‐ornithine, and the leaf extract of licorice and artichoke. In a rat model of acute liver injury, an enhanced hepatoprotective effect was found compared with garlic extract alone.